HUBUNGAN ANTARA PERSEPSI ANAK TERHADAP KEMAMPUAN YANG DIMILIKI DAN KEMAMPUAN GERAK YANG SEBENARNYA - Ahadin (Jurnal Visipena, 2011)
To examine the relationship between perceived physical competence and actual motor skill competence of the first and the second years students of primary school at primary school number 31 an Banda Aceh municipality whose ages ranged from 5 to 7 year (N=30). All students individually completed the Harter and pike (1984) Pictorial Scale of Perceived Competence and Social Acceptance (PSPCSA) was measured by using the Test of Gross Motor Development (TGMD) Ulrich, 1985. Data collected from 30 students consist of 15 boys and 15 girls, whose average age X=6.7 year, standard deviation 0.41, the boys average age X=6.87 year and the girls average age X=6.12 year. The background of the students whose father work as government official and the rest unemployed family or work at private sector. Four separate ANOVA’s were conducted to determine gender differences in perceived physical competence and actual motor skill competence: locomotor, object control, and TGMD-Total. ANOVA documented that the boys and girls did not differ in perceived physical competence, F (1,57) = 0,427;P=0,52. The object control component of actual motor skill competence differed for gender F (1,57) = 10,91; P =0,001. Gender by locomotor competence, F (1,57) = 1,96; P = 0,17 and TGMD-Total F (1,57) = 0, 73; P = 0,40. The boys actual object control motor skill competence exceeded the girls. Correlation and regression models were used to examine the influence of actual motor skill competence and gender on perceived physical competence factors were not significantly correlated with perceived physical competence. These correlation were 0,00 for locomotor and 0, 25 for TGMD – Total competence. The object control sub scale was significantly correlated r = 0,33 with perceived physical competence F ( 1,58) = 4,17 ; p = 0,05. The correlation for actual motor skill competence was low to moderately correlated with perceived physical copentence.